Engineering Sub‐Nanometer Hafnia‐Based Ferroelectric to Break The Scaling Relation for High‐Efficiency Piezocatalytic Water Splitting - Su, Ran; Zhang, Jiahui; Wong, Vienna; Zhang, Dawei; Yang, Yong; Luo, Zheng‐Dong; Wang, Xiaojing; Wen, Hui; Liu, Yang; Seidel, Jan; Yang, Xiaolong; Pan, Ying; et al. (Advanced Materials)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Rapid preparation of self-supported nickel–iron oxide as a high-performance glucose sensing platform - Ni, Ming; Tan, Minyuan; Pan, Ying; Zhu, Chuhong; Du, Haiwei (Journal of Materials Chemistry C)
Nickel–iron oxide electrocatalysts prepared via a rapid electrodeposition are promising candidates for non-enzymatic glucose sensors.
Keywords: Materials Chemistry; General Chemistry

A composite consisting of intermetallic Ni3Fe and nitrogen-doped carbon for electrocatalytic water oxidation: The effect of increased pyridinic nitrogen dopant - Liu, Dan; Zhai, Haichao; Hu, Jie; Pan, Ying; Xu, Gengsheng; Zhu, Chuhong; Yuan, Yupeng (Ceramics International)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Process Chemistry and Technology; Ceramics and Composites; Electronic; Optical and Magnetic Materials

Robust ferroelectric polarization retention in harsh environments through engineered domain wall pinning - Zhang, Dawei; Sando, Daniel; Pan, Ying; Sharma, Pankaj; Seidel, Jan (Journal of Applied Physics)
Keywords: General Physics and Astronomy

Carbon-Based Metal-Free Electrocatalysts: Past, Present, and Future - Zhai, Qingfeng; Pan, Ying; Dai, Liming (Accounts of Materials Research)
Keywords: Materials Chemistry; Polymers and Plastics; Materials Science (miscellaneous); Chemical Engineering (miscellaneous)

Strain‐Engineered Nano‐Ferroelectrics for High‐Efficiency Piezocatalytic Overall Water Splitting - Su, Ran; Wang, Zhipeng; Zhu, Lina; Pan, Ying; Zhang, Dawei; Wen, Hui; Luo, Zheng‐Dong; Li, Linglong; Li, Fa‐tang; Wu, Ming; He, Liqiang; Sharma, Pankaj; et al. (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

A universal electrochemical activation enabling lattice oxygen activation in nickel-based catalyst for efficient water oxidation - Hu, Jie; Jiang, Daochuan; Weng, Zhaoyue; Pan, Ying; Li, Zhongjun; Du, Haiwei; Yuan, Yupeng (Chemical Engineering Journal)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; Environmental Chemistry; General Chemistry

Anisotropic Ion Migration and Electronic Conduction in van der Waals Ferroelectric CuInP2S6 - Zhang, Dawei; Luo, Zheng-Dong; Yao, Yin; Schoenherr, Peggy; Sha, Chuhan; Pan, Ying; Sharma, Pankaj; Alexe, Marin; Seidel, Jan (Nano Letters)
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Synergetic modulation of the electronic structure and hydrophilicity of nickel–iron hydroxide for efficient oxygen evolution by UV/ozone treatment - Pan, Ying; Wu, Yanfang; Hsain, H. Alex; Su, Ran; Cazorla, Claudio; Chu, Dewei (Journal of Materials Chemistry A)
Enhanced OER performance of Ni(Fe) hydroxide through UV/ozone treatment.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Assessment of electrocatalytic activity through the lens of three surface area normalization techniques - Ren, Hangjuan; Pan, Ying; Sorrell, Charles C.; Du, Haiwei (Journal of Materials Chemistry A)
Electrocatalytic activities of electrodes for water splitting are assessed via geometric area, BET surface area and ECSA normalisations.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Enhanced electrocatalytic oxygen evolution by manipulation of electron transfer through cobalt-phosphorous bridging - Pan, Ying; Ren, Hangjuan; Chen, Ruizhe; Wu, Yanfang; Chu, Dewei (Chemical Engineering Journal)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; Environmental Chemistry; General Chemistry

Silver nanowire/nickel hydroxide nanosheet composite for a transparent electrode and all-solid-state supercapacitor - Du, Haojin; Pan, Ying; Zhang, Xiao; Cao, Fuyang; Wan, Tao; Du, Haiwei; Joshi, Rakesh; Chu, Dewei (Nanoscale Advances)
Silver nanowire (Ag NW) based composites have shown a great potential not just in transparent electrodes but in diverse functional applications.
Keywords: General Engineering; General Materials Science; General Chemistry; Atomic and Molecular Physics; and Optics; Bioengineering

Active site engineering by surface sulfurization for a highly efficient oxygen evolution reaction: a case study of Co3O4 electrocatalysts - Pan, Ying; Ren, Hangjuan; Du, Haiwei; Cao, Fuyang; Jiang, Yifeng; Du, Haojin; Chu, Dewei (Journal of Materials Chemistry A)
Enhanced catalytic activity of Co3O4@CoSx through surface sulfurization.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Mimicking synaptic plasticity and learning behaviours in solution processed SnO2 memristor - Pan, Ying; Wan, Tao; Du, Haiwei; Qu, Bo; Wang, Danyang; Ha, Tae-Jun; Chu, Dewei (Journal of Alloys and Compounds)
Keywords: Materials Chemistry; Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Threshold Switching Induced by Controllable Fragmentation in Silver Nanowire Networks - Wan, Tao; Pan, Ying; Du, Haiwei; Qu, Bo; Yi, Jiabao; Chu, Dewei (ACS Applied Materials & Interfaces)
Keywords: General Materials Science

The sintering behavior and mechanical properties of CaSiO3 bioceramics with B2O3 addition - Pan, Ying; Yin, J.; Zuo, K.; Yao, D.; Xia, Y.; Liang, H.; Zeng, Y. (Ceramics International)

Effects of h-BN addition on microstructures and mechanical properties of β-CaSiO3 bioceramics - Pan, Ying; Yao, D.; Zuo, K.; Xia, Y.; Yin, J.; Liang, H.; Zeng, Y. (Journal of the Mechanical Behavior of Biomedical Materials)

The improved mechanical properties of β-CaSiO3 bioceramics with Si3N4 addition - Pan, Ying; Zuo, K.; Yao, D.; Yin, J.; Xin, Y.; Xia, Y.; Liang, H.; Zeng, Y. (Journal of the Mechanical Behavior of Biomedical Materials)

Effects of silica sol on the microstructure and mechanical properties of CaSiO3 bioceramics - Pan, Ying; Yin, J.; Yao, D.; Zuo, K.; Xia, Y.; Liang, H.; Zeng, Y. (Materials Science and Engineering C)

The optical properties of low infrared transmittance WO3-x nanocrystal thin films prepared by DC magnetron sputtering under different oxygen ratios - Xin, Y.; Zhou, H.; Ni, X.; Pan, Ying; Zhang, X.; Zheng, J.; Bao, S.; Jin, P. (RSC Advances)